A comparative performance analysis of modified Dӧmӧsi’s cryptosystem and data encryption standard - Khaleel, Ghassan; Turaev, Sherzod; Mohd Tamrin, Mohd Izzuddin; Alshaikhli, Imad Fakhri Taha (2017)
The performance has a central importance for all cryptosystems. This paper aims to provide a framework and platform to evaluate a performance of Modified Dӧmӧsi’s Cryptosystem, a stream cipher based on finite automata, comparing to Data Encryption Standard. The performance is evaluated in terms of encrypting time and throughput.